2017
DOI: 10.3168/jds.2016-11944
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and bioactivities of the exopolysaccharide from a probiotic strain of Lactobacillus plantarum WLPL04

Abstract: Exopolysaccharide (EPS) was extracted and purified from Lactobacillus plantarum WLPL04, which has been confirmed previously as a potential probiotic for its antagonistic and immune-modulating activity. It has a molecular weight of 6.61 × 10 Da, consisting of xylose, glucose, and galactose in an approximate molar ratio of 3.4:1.8:1. Microstructural studies demonstrated that the EPS appeared as a smooth sheet structure with many homogeneous rod-shaped lumps. The preliminary in vitro assays indicated that the EPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 51 publications
3
79
0
5
Order By: Relevance
“…Starter culture was prepared as previously described of inoculum, then batch fermentation was performed in a 5.0L capacity fermentor (Biotech-2002; Bao Xing Bio-Engineering Equipment Co., Ltd, Shanghai, China) at 37°C with an inoculum concentration of 3.0% to obtain the fermented broth ( 15 ). Extracellular polymeric substances were obtained as described previously ( 34 ). The crude EPS fractions were separated and purified according to procedures described by Lin et al with slight modifications ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…Starter culture was prepared as previously described of inoculum, then batch fermentation was performed in a 5.0L capacity fermentor (Biotech-2002; Bao Xing Bio-Engineering Equipment Co., Ltd, Shanghai, China) at 37°C with an inoculum concentration of 3.0% to obtain the fermented broth ( 15 ). Extracellular polymeric substances were obtained as described previously ( 34 ). The crude EPS fractions were separated and purified according to procedures described by Lin et al with slight modifications ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total EPS from the SDM medium were isolated by means of double cold ethanol precipitation method without dialysis (Rimada and Abraham, 2003). The absence of protein and nucleic acids in the EPS was assessed by spectrophotometric analysis using a UV-visible spectrophotometer (Jasco V-530), at a wavelength of 260-280 nm (Liu et al, 2016).…”
Section: Eps Characterization By Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…It was suggested that EPS from L. acidophilus 10307 could induce cytotoxicity in two colon cancer cell lines, HCT15 and Caco2 cells (Deepak et al, 2016). Additionally, EPS from L. plantarum WLPL04 and L. plantarum YW32 showed significant inhibitory effects on HT-29 colon cancer cells (Wang et al, 2015b;Liu et al, 2017); EPS from L. plantarum RJF 4 displayed antitumoral activity in pancreatic cancer cells (Dilna et al, 2015). cell-bound EPS from L. rhamnosus ATCC 9595 could inhibit the growth of PANC1 and HT-29 cancer cells (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%